DAMPAK PROGRAM MEMBINA EKONOMI KELUARGA SEJAHTERA (MEKAAR) TERHADAP PENINGKATAN PENDAPATAN MASYARAKAT DI KOTA BINJAI - Merry Moy Mita; Bertha Nerphy Siahaan (SUAN PUBLISHER, 2025)
This study aims to analyze the impact of the Membina Ekonomi Keluarga Sejahtera (Mekaar) program on increasing household income among communities in Binjai City, Indonesia. The research is motivated by the need to address limited access to micro-capital and entrepreneurship development among low-income families, especially women-led households. Using a quantitative explanatory approach, data were collected through surveys from 150 respondents who had participated in the Mekaar program for at least one year. The data were analyzed using multiple linear regression with SPSS version 26. The results show that the Mekaar program has a positive and significant effect on income improvement, with a coefficient of determination (R²) of 0.612. The variables of microcredit, group mentoring, and entrepreneurship training all contributed significantly, with financing having the highest influence (β = 0.412, p < 0.05). These findings confirm the research hypothesis and indicate that a well-integrated microfinance program can substantially enhance the economic capacity of underprivileged communities. The study supports existing literature on community-based economic empowerment and contributes to the evaluation of microfinance programs in urban areas. Practically, this research offers recommendations for strengthening mentoring quality and the sustainability of business training. Academically, it provides empirical support for the role of microfinance in local economic development strategies.